2022
DOI: 10.1088/1361-6463/ac87bb
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature characteristics and gate leakage mechanisms of LPCVD-SiNx/AlGaN/GaN MIS-HEMTs

Abstract: In this paper, we systematically investigated the static properties and gate current mechanism of LPCVD-SiNx/AlGaN/GaN MIS-HEMTs at cryogenic temperature range from 10 K to 300 K. It is found that the threshold voltage of the device shows a positive shift due to the increased intrinsic carrier concentration at low temperature, and both the maximum transconductance and ON-resistance are improved at the low temperatures because of the enhanced electron mobility. Under very low electric field, the gate leakage ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They are essentially suitable for various applications targeting low losses and high operating frequencies and temperatures. This special issue evaluates a series of GaN-and AlGaN-based electronic devices proposed by Chinese researchers, such as Schottky barrier diodes (SBDs) [19], metal-oxide-semiconductor field effect transistors (MOSFETs) [20], high electron mobility transistors (HEMTs) [21][22][23][24][25], and so forth.…”
Section: Electronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are essentially suitable for various applications targeting low losses and high operating frequencies and temperatures. This special issue evaluates a series of GaN-and AlGaN-based electronic devices proposed by Chinese researchers, such as Schottky barrier diodes (SBDs) [19], metal-oxide-semiconductor field effect transistors (MOSFETs) [20], high electron mobility transistors (HEMTs) [21][22][23][24][25], and so forth.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…By adopting a p-NiO x gate cap layer and an ultra-thin AlGaN barrier layer, Du et al [21] proposed an etching-free fabrication method for a normally-off GaN HEMT design. Guo et al [22] investigated the static properties and gate current mechanism of SiN x /AlGaN/GaN metal-insulator-semiconductor HEMTs using low-pressure chemical vapor deposition. They found that, at low temperatures, the device's threshold voltage shifts positively, and both maximum transconductance and ON-resistance significantly improve.…”
Section: Electronic Devicesmentioning
confidence: 99%